Preliminary studies on the inhibition potential of Indian domestic curd against coliforms, an emerging periodontal pathogen - Surajit Debnath (Wolters Kluwer Medknow Publications, 2017)
Background: Coliforms colonize in dental plaques via oral route and may lead to systemic complications. Escherichia coli and its lipopolysaccharide-induced periodontitis is an emerging threat. Clinical management necessitates antibiotic regimens with risk of resistance and upsetting the gut. There is urgent need for better, sustainable, and economical alternative. Aim: To investigate the inhibition of coliforms, a potential periodontopathogen directly by Indian domestic curd (IDC) "in situ". Materials and Methods: Coliforms from natural habitat (Municipal sewage in Agartala, Tripura), a source of infection through food and water, were used as target organism. Domestically prepared curd without any fortification is used to explore its true inhibition potential. Assays of agar well diffusion performed with IDC (ultraviolet sterilized and pH adjusted 6.5) against isolated pure cultures of coliforms. The study protocol nullified effect of organic acids, volatile compounds, bacteriophages, and peroxides in IDC. Peptide nature of inhibitory ingredient was studied by Sodium Dodecyle Sulphate Polyacrylamide Gel Electrophoresis (SDS-PAGE), urea treatment. Computational phylogenetics revealed structural features of inhibitory ingredient. Statistical comparisons were done by analysis of variance. Second-order polynomial regression was done to evaluate the effect of IDC dilution on coliform inhibition. Mann-Whitney U-test performed to analyze different sample treatments. Results: Agar well diffusion (sealed bottom wells) shows inhibition of catalase-negative coliforms (confirmed by Gram staining and triple sugar iron agar assay) in pure culture (MacConkey agar). Activity diminished in urea, potentiated in ethylene diamine tetra acetic acid, remains unchanged by heat treatment (121°C, 15 min). SDS-PAGE revealed three distinct peptides (>10-15KDa). Hence, thermostable inhibitory peptides attached to target cell lead to observed activity (titer up to 1204.82 AU/ml with minimum 8 mm inhibition). Conclusions: IDC adequately inhibits sewage coliforms and may prevent dental plaques coliform colonization and its associated risks.